Z badań nad warsztatem historycznym księcia Adama Jerzego Czartoryskiego ("Wstęp do historii litewskiej", rozdz. I, s. 1-8) - Otorowski, Michał (Colloquia Litteraria, 2018)
Wstęp do historii litewskiej [An Outline of the Lithuanian History] by Adam Jerzy Czartoryski has never been published before, it has not been analyzed, it has not been taken in consideration while dealing with texts on Polish, Belorussian and Lithuanian historiography, nor in the research into Count Adam Jerzy Czartoryski’s activities as the Curator in Wilno [Vilniaus]. Czartoryski’s historical treatise, which provides an outline of the history of Wielkie Księstwo Litewskie [the Grand Duchy of Lithuania], reveals in a unique way the historical and philosophical method of Adam Jerzy Czartoryski, who is still unknown to the general public as an author. Comparing Czartoryski’s book with the canonical works of historiography allows for an analysis of the process of Czartoryski’s connection of history with politics and political thinking. Concrete problems of historiography which Czartoryski faced could be clearly seen, particularly in his non-scholarly goal of his book: to show the differences in the civilizational foundations of Lithuania from Belorussian and Russian influences. Czartoryski in this way was combating weird plans to recreate the Grand Duchy of Lithuania under the Romonov’s rule. This paper contains a fragment of a commentary to Duke Czartoryski’s treatise covering eight subchapters.